Anti-crack mortar for assembly type light partition board and preparation method of anti-crack mortar
By optimizing the crack-resistant mortar formula and process, the durability problem of traditional reinforced concrete structures under chemical erosion is solved, the service life and construction efficiency of the building are improved, and the reuse of solid waste and environmentally friendly production are achieved.
Patent Information
- Application Number
- CN202310831894.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-07
- Publication Date
- 2025-01-07
AI Technical Summary
Traditional reinforced concrete structures are prone to durability failure under chemical erosion such as freeze-thaw, dry-wet cycle, chloride ions, sulfates, etc., resulting in building corrosion and cracks, affecting service life and economic costs.
A prefabricated lightweight partition wall panel mortar is adopted, including silicate cement, redispersible latex powder, hydroxypropyl methyl cellulose ether, gypsum powder, fly ash, crack-resistant fibers, polystyrene particles , light mineral waste slag and a variety of additives, through the optimization of formula and process, the mortar's crack resistance, waterproofing, durability and construction performance are improved.
It effectively solves the problems of poor waterproofness and hollow wall cracking of traditional mortars, improves the service life of buildings, reduces construction costs and resource consumption, and realizes the comprehensive reuse of solid waste and environmentally friendly production.
Smart Images

Figure BDA0004327364590000161 
Figure BDA0004327364590000171
Abstract
Description
[Technical field]
[0001] The invention belongs to the technical field of building materials, and particularly relates to an anti-cracking mortar for assembled lightweight partition boards and a preparation method thereof. [Background technology]
[0002] As the most widely used building structure in civil construction, reinforced concrete structure is widely used in related fields such as construction, water conservancy projects, roads, bridge projects, etc. Due to the influence of freeze-thaw, dry-wet cycle, chloride ion, sulfate and other chemical erosion, the building fails to maintain its service life, the steel bars inside the building are corroded, and the surrounding concrete is seriously corroded, which damages the durability of the building, thus affecting the normal use of the building and causing huge economic losses.
[0003] Prefabricated buildings have the advantages of light weight, high strength, flexible layout, safety and reliability, low carbon and environmental protection, and reusability. They are a hot spot and trend in the development of the construction industry. In recent years, prefabricated buildings have developed rapidly in my country and have become one of the directions for the transformation and upgrading of the construction industry. Mortar, as the main building material in the preparation of prefabricated partition boards, has a wide variety and huge usage. Its performance continues to improve with the improvement of technical level.
[0004] Anti-crack mortar is a new type of green and environmentally friendly building material that can replace traditional cement mortar. It can be used for masonry and plastering. The partition board prepared by it is not only light in texture, but also effectively solves the corrosion and rust problems of traditional reinforced concrete structures, greatly reducing the time spent in the construction process. From the perspective of preparation technology, it not only saves resources, but also is simple to operate, green and environmentally friendly, and has high preparation efficiency. [Summary of the invention]
[0005] In order to promote the renewal of traditional mortar, continuously upgrade to meet market demand and save economic costs, the purpose of the present invention is to provide an anti-cracking mortar for assembled lightweight partition boards with good use effect and excellent anti-cracking performance.
[0006] Another object of the present invention is to provide a method for preparing anti-cracking mortar for assembled lightweight partition boards. The preparation method is simple to operate, convenient to control, has high production efficiency, low production cost, and can be used for large-scale production.
[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0008] An anti-cracking mortar for assembled lightweight partition boards comprises the following raw materials in parts by weight: 1600-2800 parts of silicate cement, 1-50 parts of redispersible latex powder, 1-50 parts of hydroxypropyl methylcellulose ether, 800-1500 parts of gypsum powder, 1200-2400 parts of fly ash, 8-40 parts of anti-cracking fibers, 1200-3000 parts of water, 2000-3200 parts of polystyrene particles, 600-1800 parts of light mineral waste residue, 2-3 parts of foaming agent, 2-3 parts of early strength agent, 2-3 parts of foam stabilizer, 2-3 parts of waterproofing agent, 2-3 parts of water reducing agent, 2-3 parts of accelerating setting agent and 2-3 parts of reinforcing agent.
[0009] Furthermore, the anti-cracking fiber is polypropylene anti-cracking fiber.
[0010] Furthermore, the foaming agent is a polyurethane foam foaming agent.
[0011] Furthermore, the early strength agent is a calcium chloride antifreeze agent.
[0012] Furthermore, the foam stabilizer is a foam enhancing and stabilizing agent.
[0013] Furthermore, the waterproofing agent is a mortar waterproofing agent.
[0014] Furthermore, the water reducer is a naphthalene-based high-efficiency water reducer.
[0015] Furthermore, the quick-setting agent is a liquid quick-setting agent.
[0016] Furthermore, the reinforcing agent is KFA cement admixture.
[0017] After long-term research, the present invention optimizes and screens a variety of additives (foaming agent, early strength agent, foam stabilizer, waterproofing agent, water reducer, quick setting agent, reinforcing agent) so that the anti-cracking mortar for assembled lightweight partition boards prepared by the present invention has excellent performance to meet the use requirements. The technical principle of the present invention is:
[0018] The polyurethane foam blowing agent selected by the present invention is a chemical used to prepare polyurethane foam, and its main components are isocyanate and polyol. After the blowing agent is mixed with other chemicals, a chemical reaction between the isocyanate and the polyol occurs, generating gas and forming a foam structure.
[0019] The calcium chloride antifreeze agent selected by the present invention has a slow setting effect and can improve the early strength of concrete.
[0020] The foam enhancing and stabilizing agent selected by the present invention can reduce the solid-liquid-gas surface tension, and the material that improves the strength of the bubble film can play the role of foaming and stabilizing.
[0021] The foam increasing and stabilizing agent is selected from one of dodecyl dimethyl amine oxide, dodecyl trimethyl ammonium bromide, hexadecyl trimethyl ammonium chloride and octadecyl dimethyl amine oxide.
[0022] The mortar waterproofing agent (FS101 mortar waterproofing agent) selected by the present invention can inhibit or reduce the voids in the cement mortar through the strong physical and chemical action between the emulsion particles and the cement, and prevent the penetration of water with strong waterproofing properties.
[0023] The liquid quick-setting agent selected by the present invention can make concrete or mortar set and harden quickly in a short time and produce higher early strength.
[0024] The quick-setting agent is a liquid quick-setting agent, including one or more of water glass type, aluminate type, aluminum sulfate type and aluminum hydroxide type.
[0025] The KFA cement admixture selected by the present invention can produce an electrochemical reaction to decompose cement particles, so that the metal elements in the cement can play a role, thereby completely hydrating the cement particles and achieving the maximum utilization efficiency of the cement.
[0026] The liquid quick-setting agent selected by the present invention and the calcium chloride antifreeze agent work synergistically with each other to make the early strength of the material higher.
[0027] The mortar of the present invention is a new type of environmentally friendly building material made by mixing silicate cement, redispersible latex powder, hydroxypropyl methylcellulose ether, construction-grade gypsum, fly ash, anti-cracking fiber, expanded polystyrene particles, and additives. The cement mortar has the characteristics of light texture, crack resistance, combustion resistance, moisture resistance, waterproofness, and reuse. It not only effectively solves the construction quality problems such as the poor waterproofness of traditional mortar, hollowing and cracking of walls, but also makes solid wastes comprehensively reused, protects the environment, saves resources, and has obvious economic and social benefits. It effectively solves the problem of solid waste utilization that cannot be achieved due to the limitations of the prior art. The cement mortar of the present invention is simple to prepare, convenient to obtain materials, low production cost, and has the characteristics of small bulk density, small unit construction area consumption, low construction cost, etc., and has broad market prospects.
[0028] The present invention also provides a method for preparing anti-cracking mortar for assembled lightweight partition boards, comprising the following steps:
[0029] Step 1: Clean the mixer and check to make sure it is operating normally;
[0030] Step 2: weigh the weight of each component according to the above components;
[0031] Step 3: crush the weighed light mineral waste slag, and sieve it through a sieve of ≤3 mm to obtain light mineral waste slag powder;
[0032] Step 4: first add weighed silicate cement, redispersible latex powder, hydroxypropyl methylcellulose ether, fly ash, gypsum powder, anti-cracking fiber and the light mineral waste slag powder obtained in step 3 into a mixer, stir in the mixer to fully mix the materials, and prepare a mixture a;
[0033] Step 5, adding a foaming agent, an early strength agent, a foam stabilizer, a reinforcing agent and water to the mixture a obtained in step 4, and then stirring in a mixer to obtain a mixture b;
[0034] Step 6: adding a waterproofing agent, a water reducing agent, an accelerating setting agent and polystyrene particles into water and stirring with a stirrer to obtain a mixture c;
[0035] Step 7, adding the mixture c obtained in step 6 to the mixture b obtained in step 5, starting the mixer to stir and mix, to obtain a mixture d;
[0036] Step 8: Test the viscosity of the mixture d and complete the mortar preparation.
[0037] Compared with the prior art, the present invention has the following advantages:
[0038] (1) The present invention uses light mineral waste slag to replace part of cement as filler to improve the compressive strength of wallboards. Selecting low-cost and widely available solid waste slag and other pollutants as auxiliary materials to improve the compressive strength of wallboards not only effectively solves the common quality problems of hollowing and cracking of wall plastering caused by poor water retention and large shrinkage after drying of cement mortar, but also makes comprehensive reuse of solid waste, protects the environment, and saves resources.
[0039] (2) The optimized and selected redispersible latex powder and hydroxypropyl methylcellulose ether of the present invention can increase the bonding force between the dry materials of the mortar and reduce the peeling, bulging and cracking phenomena during curing. Construction-grade gypsum powder can increase the mechanical strength of the mortar, delay the setting time of the mortar, and avoid material loss caused by too fast setting of the mortar during construction.
[0040] (3) The polystyrene particles optimized and selected by the present invention can significantly reduce the weight of mortar, greatly increase the wallboard unit construction area usage, and achieve energy-saving and environmental protection effects. The expanded polystyrene particles as solid fillers enhance the waterproof and thermal insulation properties of the wallboard, effectively preventing the wallboard from absorbing water and cracking, and leaking due to moisture on cloudy days.
[0041] (4) The polypropylene anti-cracking fiber optimized and screened in the present invention can improve the bonding strength and cohesion of the mortar, reduce the internal stress of the mortar, and prevent stress cracking after the mortar is cured.
[0042] (5) The use of fly ash in the present invention can not only realize waste utilization, reduce cement consumption, and reduce mortar costs, but also fly ash has high efficiency in water reduction, which reduces the water content of mortar and reduces the weight of mortar.
[0043] (6) The mixing of various additives in the present invention plays a synergistic role in modifying silicate cement, thereby obtaining advantages in mechanical properties, durability, construction performance, etc. of the mortar, effectively improving the chemical corrosion resistance of the mortar matrix and increasing the service life of the building.
[0044] (7) Compared with other mortars for prefabricated partition boards, the mortar of the present invention is able to produce prefabricated wall panels with small size, less occupied building space, light weight, no need for wet work and sporadic masonry construction, and more importantly, no need to use a large amount of sand and stone, thus achieving the common advantages of light weight and strong quality, and effectively reducing the use of non-renewable resources.
[0045] (8) Compared with other mortars for assembled partition boards, the present invention has outstanding energy-saving and waste-utilizing characteristics in the production process. Partition boards that fail in the production process, raw materials that are polluted and wasted in the production process, and partition boards that reach the end of their service life after assembly can all be recycled and reused. Production waste and wallboards that have reached the end of their service life can be recycled, crushed, screened, and finally used as raw materials to produce new wallboards, achieving a recycling rate of more than 65% in the production process, effectively avoiding environmental pollution and waste of resources, and achieving green and environmentally friendly production.
[0046] (9) The mortar of the present invention can be used to manufacture lightweight partition boards or to connect two lightweight wall materials. The wall materials produced by the mortar have a simple manufacturing process and are easy to be renovated later. The problems of surface cracking, water seepage, and moisture susceptibility of traditional wall panels are solved. Compared with traditional wall panels, the mortar has the advantages of being lightweight, flame resistant, and highly permeable. The production process is pollution-free, and the finished wall materials are easy to use during the construction process, and have strong practical value. [Specific implementation method]
[0047] In order to facilitate a better understanding of the present invention, the following examples are used to illustrate the present invention. These examples belong to the protection scope of the present invention, but do not limit the protection scope of the present invention.
[0048] In an embodiment of the present invention, the anti-cracking mortar for the assembled lightweight partition board comprises the following raw materials in parts by weight: 1600-2800 parts of silicate cement, 1-50 parts of redispersible latex powder, 1-50 parts of hydroxypropyl methylcellulose ether, 800-1500 parts of gypsum powder, 1200-2400 parts of fly ash, 8-40 parts of anti-cracking fiber, 1200-3000 parts of water, 2000-3200 parts of polystyrene particles, 600-1800 parts of light mineral waste residue, 2-3 parts of foaming agent, 2-3 parts of early strength agent, 2-3 parts of foam stabilizer, 2-3 parts of waterproofing agent, 2-3 parts of water reducer, 2-3 parts of accelerating setting agent, and 2-3 parts of reinforcing agent;
[0049] The redispersible latex powder is vinyl acetate-ethylene copolymer;
[0050] The viscosity of the hydroxypropyl methylcellulose ether is 100,000-300,000;
[0051] The anti-cracking fiber is a polypropylene anti-cracking fiber, and the length of the polypropylene anti-cracking fiber is 6-10mm;
[0052] The fly ash is Class II fly ash;
[0053] The light mineral waste slag is blast furnace slag or boiler bottom slag or light mineral waste slag;
[0054] The foaming agent is a polyurethane foam foaming agent;
[0055] The early strength agent is calcium chloride antifreeze;
[0056] The foam stabilizer is a foam increasing and stabilizing agent, and the foam increasing and stabilizing agent is selected from one or more of dodecyl dimethyl amine oxide, dodecyl trimethyl ammonium bromide, hexadecyl trimethyl ammonium chloride, and octadecyl dimethyl amine oxide;
[0057] The waterproofing agent is a mortar waterproofing agent, and the mortar waterproofing agent is FS101 mortar waterproofing agent;
[0058] The water reducing agent is a naphthalene-based high-efficiency water reducing agent;
[0059] The quick-setting agent is a liquid quick-setting agent, including one or more of water glass type, aluminate type, aluminum sulfate type and aluminum hydroxide type;
[0060] The reinforcing agent is KFA cement admixture;
[0061] The method for preparing the anti-cracking mortar for the assembled lightweight partition board comprises the following steps:
[0062] Step 1: Clean the mixer and check to make sure it is operating normally;
[0063] Step 2: weigh the weight of each component according to the above components;
[0064] Step 3: crush the weighed light mineral waste slag, and sieve it through a sieve of ≤3 mm to obtain light mineral waste slag powder;
[0065] Step 4: first add weighed silicate cement, redispersible latex powder, hydroxypropyl methylcellulose ether, fly ash, gypsum powder, anti-cracking fiber and the light mineral waste slag powder obtained in step 3 into a mixer, stir in the mixer to fully mix the materials, and prepare a mixture a;
[0066] Step 5, adding a foaming agent, an early strength agent, a foam stabilizer, a reinforcing agent and water to the mixture a obtained in step 4, and then stirring in a mixer to obtain a mixture b;
[0067] Step 6: adding a waterproofing agent, a water reducing agent, an accelerating setting agent and polystyrene particles into water and stirring with a stirrer to obtain a mixture c;
[0068] Step 7, adding the mixture c obtained in step 6 to the mixture b obtained in step 5, starting the mixer to stir and mix, to obtain a mixture d;
[0069] Step 8: Test the viscosity of the mixture d and complete the mortar preparation.
[0070] The following is explained with more specific examples.
[0071] Example 1
[0072] An anti-cracking mortar for assembled lightweight partition boards, comprising the following raw materials in parts by weight: 1600 parts of ordinary Portland cement, 5 parts of redispersible latex powder, 5 parts of hydroxypropyl methylcellulose ether, 800 parts of construction-grade gypsum powder, 1400 parts of fly ash, 10 parts of polypropylene anti-cracking fiber, 1600 parts of water, 2000 parts of polystyrene particles, 600 parts of light mineral waste residue, 2 parts of foaming agent, 3 parts of early strength agent, 2 parts of foam stabilizer, 2 parts of waterproofing agent, 2 parts of water reducing agent, 2 parts of accelerating setting agent, and 2 parts of reinforcing agent;
[0073] The redispersible latex powder is vinyl acetate-ethylene copolymer;
[0074] The viscosity of the hydroxypropyl methylcellulose ether is 150,000;
[0075] The anti-cracking fiber is a polypropylene anti-cracking fiber, and the length of the polypropylene anti-cracking fiber is 8 mm;
[0076] The fly ash is Class II fly ash;
[0077] The light mineral waste slag is blast furnace slag;
[0078] The foaming agent is a polyurethane foam foaming agent;
[0079] The early strength agent is calcium chloride antifreeze;
[0080] The foam stabilizer is a foam increasing and stabilizing agent, and the foam increasing and stabilizing agent is selected from dodecyl trimethyl ammonium bromide;
[0081] The waterproofing agent is a mortar waterproofing agent, and the mortar waterproofing agent is FS101 mortar waterproofing agent;
[0082] The water reducing agent is a naphthalene-based high-efficiency water reducing agent;
[0083] The quick-setting agent is a liquid quick-setting agent, and the liquid quick-setting agent is an aluminum hydroxide type;
[0084] The reinforcing agent is KFA cement admixture;
[0085] The method for preparing the anti-cracking mortar for the assembled lightweight partition board comprises the following steps:
[0086] Step 1: Clean the mixer and check to make sure it is operating normally;
[0087] Step 2: weigh the weight of each component according to the above components;
[0088] Step 3: crush the weighed light mineral waste slag, and sieve it through a sieve of ≤3 mm to obtain light mineral waste slag powder;
[0089] Step 4: first add weighed silicate cement, redispersible latex powder, hydroxypropyl methylcellulose ether, fly ash, construction-grade gypsum powder, polypropylene anti-cracking fiber and the light mineral waste powder obtained in step 3 into a mixer, and stir the mixer at a speed of 50 revolutions per minute for 10 minutes to fully mix the materials;
[0090] Step 5: Add 800 parts of foaming agent, early strength agent, foam stabilizer, enhancer and water, and stir at a speed of 200 revolutions per minute for 8 minutes in a mixer;
[0091] Step 6: Add waterproofing agent, water reducing agent, quick setting agent and polystyrene particles into 800 parts of water and stir rapidly for 5 minutes using a handheld electric stirrer;
[0092] Step 7: Add the mixture in step 6 to the mixer to mix with the mixture in step 5, start the mixer, and mix thoroughly at 300 rpm for 10 minutes;
[0093] Step 8: Test the mortar viscosity and complete the mortar preparation.
[0094] After the mortar is prepared, it should be poured and used in time to avoid the mortar being left for a long time to solidify and stick to the mixer or container.
[0095] Example 2
[0096] An anti-cracking mortar for assembled lightweight partition boards, comprising the following raw materials in parts by weight: 1800 parts of ordinary Portland cement, 8 parts of redispersible latex powder, 8 parts of hydroxypropyl methylcellulose ether, 1000 parts of construction-grade gypsum powder, 1800 parts of fly ash, 15 parts of polypropylene anti-cracking fiber, 2000 parts of water, 2400 parts of polystyrene particles, 800 parts of light mineral waste residue, 2 parts of foaming agent, 3 parts of early strength agent, 2 parts of foam stabilizer, 2 parts of waterproofing agent, 2 parts of water reducing agent, 2 parts of accelerating setting agent, and 3 parts of reinforcing agent;
[0097] The redispersible latex powder is vinyl acetate-ethylene copolymer;
[0098] The viscosity of the hydroxypropyl methylcellulose ether is 150,000;
[0099] The anti-cracking fiber is a polypropylene anti-cracking fiber, and the length of the polypropylene anti-cracking fiber is 8 mm;
[0100] The fly ash is Class II fly ash;
[0101] The light mineral waste slag is boiler bottom slag;
[0102] The foaming agent is a polyurethane foam foaming agent;
[0103] The early strength agent is calcium chloride antifreeze;
[0104] The foam stabilizer is a foam increasing and stabilizing agent, and the foam increasing and stabilizing agent is selected from dodecyl dimethyl amine oxide;
[0105] The waterproofing agent is a mortar waterproofing agent, and the mortar waterproofing agent is FS101 mortar waterproofing agent;
[0106] The water reducing agent is a naphthalene-based high-efficiency water reducing agent;
[0107] The quick-setting agent is a liquid quick-setting agent, and the liquid quick-setting agent is a water glass type;
[0108] The reinforcing agent is KFA cement admixture;
[0109] The method for preparing the anti-cracking mortar for the assembled lightweight partition board comprises the following steps:
[0110] Step 1: Clean the mixer and check to make sure it is operating normally;
[0111] Step 2: weigh the weight of each component according to the above components;
[0112] Step 3: crush the weighed light mineral waste slag, and sieve it through a sieve of ≤3 mm to obtain light mineral waste slag powder;
[0113] Step 4: first add weighed silicate cement, redispersible latex powder, hydroxypropyl methylcellulose ether, fly ash, construction-grade gypsum powder, polypropylene anti-cracking fiber and the light mineral waste powder obtained in step 3 into a mixer, and stir the mixer at a speed of 50 revolutions per minute for 10 minutes to fully mix the materials;
[0114] Step 5: Add 1000 parts of foaming agent, early strength agent, foam stabilizer, enhancer and water, and stir at a speed of 200 revolutions per minute for 8 minutes in a mixer;
[0115] Step 6: Add waterproofing agent, water reducing agent, quick setting agent and polystyrene particles into 1000 parts of water and stir rapidly for 5 minutes using a handheld electric stirrer;
[0116] Step 7: Add the mixture in step 6 to the mixer to mix with the mixture in step 5, start the mixer, and mix thoroughly at 300 rpm for 10 minutes;
[0117] Step 8: Test the mortar viscosity and complete the mortar preparation.
[0118] After the mortar is prepared, it should be poured and used in time to avoid the mortar being left for a long time to solidify and stick to the mixer or container.
[0119] Example 3
[0120] An anti-cracking mortar for assembled lightweight partition boards, comprising the following raw materials in parts by weight: 2000 parts of ordinary Portland cement, 16 parts of redispersible latex powder, 12 parts of hydroxypropyl methylcellulose ether, 1000 parts of construction-grade gypsum powder, 2000 parts of fly ash, 20 parts of polypropylene anti-cracking fiber, 2200 parts of water, 2600 parts of polystyrene particles, 1000 parts of light mineral waste residue, 2 parts of foaming agent, 2 parts of early strength agent, 2 parts of foam stabilizer, 2 parts of waterproofing agent, 2 parts of water reducing agent, 2 parts of accelerating setting agent, and 2 parts of reinforcing agent;
[0121] The redispersible latex powder is vinyl acetate-ethylene copolymer;
[0122] The viscosity of the hydroxypropyl methylcellulose ether is 150,000;
[0123] The anti-cracking fiber is a polypropylene anti-cracking fiber, and the length of the polypropylene anti-cracking fiber is 8 mm;
[0124] The fly ash is Class II fly ash;
[0125] The light mineral waste slag is light mineral waste slag;
[0126] The foaming agent is a polyurethane foam foaming agent;
[0127] The early strength agent is calcium chloride antifreeze;
[0128] The foam stabilizer is a foam increasing and stabilizing agent, and the foam increasing and stabilizing agent is selected from hexadecyltrimethylammonium chloride;
[0129] The waterproofing agent is a mortar waterproofing agent, and the mortar waterproofing agent is FS101 mortar waterproofing agent;
[0130] The water reducing agent is a naphthalene-based high-efficiency water reducing agent;
[0131] The quick-setting agent is a liquid quick-setting agent, and the liquid quick-setting agent is an aluminum sulfate type;
[0132] The reinforcing agent is KFA cement admixture;
[0133] The method for preparing the anti-cracking mortar for the assembled lightweight partition board comprises the following steps:
[0134] Step 1: Clean the mixer and check to make sure it is operating normally;
[0135] Step 2: weigh the weight of each component according to the above components;
[0136] Step 3: crush the weighed light mineral waste slag, and sieve it through a sieve of ≤3 mm to obtain light mineral waste slag powder;
[0137] Step 4: first add weighed silicate cement, redispersible latex powder, hydroxypropyl methylcellulose ether, fly ash, construction-grade gypsum powder, polypropylene anti-cracking fiber and the light mineral waste powder obtained in step 3 into a mixer, and stir the mixer at a speed of 50 revolutions per minute for 10 minutes to fully mix the materials;
[0138] Step 5: Add 1200 parts of foaming agent, early strength agent, foam stabilizer, enhancer and water, and stir at a speed of 200 revolutions per minute for 8 minutes in a mixer;
[0139] Step 6: Add waterproofing agent, water reducing agent, quick setting agent and polystyrene particles into 1000 parts of water and stir rapidly for 5 minutes using a handheld electric stirrer;
[0140] Step 7: Add the mixture in step 6 to the mixer to mix with the mixture in step 5, start the mixer, and mix thoroughly at 300 rpm for 10 minutes;
[0141] Step 8: Test the mortar viscosity and complete the mortar preparation.
[0142] After the mortar is prepared, it should be poured and used in time to avoid the mortar being left for a long time to solidify and stick to the mixer or container.
[0143] Example 4
[0144] An anti-cracking mortar for assembled lightweight partition boards, comprising the following raw materials in parts by weight: 2400 parts of ordinary Portland cement, 20 parts of redispersible latex powder, 16 parts of hydroxypropyl methylcellulose ether, 1000 parts of construction-grade gypsum powder, 2000 parts of fly ash, 24 parts of polypropylene anti-cracking fiber, 2400 parts of water, 2600 parts of polystyrene particles, 1000 parts of light mineral waste residue, 2 parts of foaming agent, 2 parts of early strength agent, 2 parts of foam stabilizer, 3 parts of waterproofing agent, 3 parts of water reducing agent, 2 parts of accelerating setting agent, and 3 parts of reinforcing agent;
[0145] The redispersible latex powder is vinyl acetate-ethylene copolymer;
[0146] The viscosity of the hydroxypropyl methylcellulose ether is 150,000;
[0147] The anti-cracking fiber is a polypropylene anti-cracking fiber, and the length of the polypropylene anti-cracking fiber is 8 mm;
[0148] The fly ash is Class II fly ash;
[0149] The light mineral waste slag is boiler bottom slag;
[0150] The foaming agent is a polyurethane foam foaming agent;
[0151] The early strength agent is calcium chloride antifreeze;
[0152] The foam stabilizer is a foam increasing and stabilizing agent, and the foam increasing and stabilizing agent is selected from dodecyl dimethyl amine oxide;
[0153] The waterproofing agent is a mortar waterproofing agent, and the mortar waterproofing agent is FS101 mortar waterproofing agent;
[0154] The water reducing agent is a naphthalene-based high-efficiency water reducing agent;
[0155] The quick-setting agent is a liquid quick-setting agent, and the liquid quick-setting agent is an aluminate type;
[0156] The reinforcing agent is KFA cement admixture;
[0157] The method for preparing the anti-cracking mortar for the assembled lightweight partition board comprises the following steps:
[0158] Step 1: Clean the mixer and check to make sure it is operating normally;
[0159] Step 2: weigh the weight of each component according to the above components;
[0160] Step 3: crush the weighed light mineral waste slag, and sieve it through a sieve of ≤3 mm to obtain light mineral waste slag powder;
[0161] Step 4: first add weighed silicate cement, redispersible latex powder, hydroxypropyl methylcellulose ether, fly ash, construction-grade gypsum powder, polypropylene anti-cracking fiber and the light mineral waste powder obtained in step 3 into a mixer, and stir the mixer at a speed of 50 revolutions per minute for 10 minutes to fully mix the materials;
[0162] Step 5: Add 1400 parts of foaming agent, early strength agent, foam stabilizer, enhancer and water, and stir at a speed of 200 revolutions per minute for 8 minutes in a mixer;
[0163] Step 6: Add waterproofing agent, water reducing agent, quick setting agent and polystyrene particles into 1000 parts of water and stir rapidly for 5 minutes using a handheld electric stirrer;
[0164] Step 7: Add the mixture in step 6 to the mixer to mix with the mixture in step 5, start the mixer, and mix thoroughly at 300 rpm for 10 minutes;
[0165] Step 8: Test the mortar viscosity and complete the mortar preparation.
[0166] After the mortar is prepared, it should be poured and used in time to avoid the mortar being left for a long time to solidify and stick to the mixer or container.
[0167] Example 5
[0168] An anti-cracking mortar for assembled lightweight partition boards, comprising the following raw materials in parts by weight: 2600 parts of ordinary Portland cement, 20 parts of redispersible latex powder, 20 parts of hydroxypropyl methylcellulose ether, 1200 parts of construction-grade gypsum powder, 2400 parts of fly ash, 28 parts of polypropylene anti-cracking fiber, 3000 parts of water, 3000 parts of polystyrene particles, 1200 parts of light mineral waste residue, 3 parts of foaming agent, 2 parts of early strength agent, 3 parts of foam stabilizer, 3 parts of waterproofing agent, 2 parts of water reducing agent, 2 parts of accelerating setting agent, and 2 parts of reinforcing agent;
[0169] The redispersible latex powder is vinyl acetate-ethylene copolymer;
[0170] The viscosity of the hydroxypropyl methylcellulose ether is 150,000;
[0171] The anti-cracking fiber is a polypropylene anti-cracking fiber, and the length of the polypropylene anti-cracking fiber is 8 mm;
[0172] The fly ash is Class II fly ash;
[0173] The light mineral waste slag is blast furnace slag;
[0174] The foaming agent is a polyurethane foam foaming agent;
[0175] The early strength agent is calcium chloride antifreeze;
[0176] The foam stabilizer is a foam increasing and stabilizing agent, and the foam increasing and stabilizing agent is selected from octadecyl dimethyl amine oxide;
[0177] The waterproofing agent is a mortar waterproofing agent, and the mortar waterproofing agent is FS101 mortar waterproofing agent;
[0178] The water reducing agent is a naphthalene-based high-efficiency water reducing agent;
[0179] The quick-setting agent is a liquid quick-setting agent, and the liquid quick-setting agent is an aluminum sulfate type;
[0180] The reinforcing agent is KFA cement admixture;
[0181] The method for preparing the anti-cracking mortar for the assembled lightweight partition board comprises the following steps:
[0182] Step 1: Clean the mixer and check to make sure it is operating normally;
[0183] Step 2: weigh the weight of each component according to the above components;
[0184] Step 3: crush the weighed light mineral waste slag, and sieve it through a sieve of ≤3 mm to obtain light mineral waste slag powder;
[0185] Step 4: first add weighed silicate cement, redispersible latex powder, hydroxypropyl methylcellulose ether, fly ash, construction-grade gypsum powder, polypropylene anti-cracking fiber and the light mineral waste powder obtained in step 3 into a mixer, and stir the mixer at a speed of 50 revolutions per minute for 10 minutes to fully mix the materials;
[0186] Step 5: Add 1500 parts of foaming agent, early strength agent, foam stabilizer, enhancer and water, and stir at a speed of 200 revolutions per minute for 8 minutes in a mixer;
[0187] Step 6: Add the waterproofing agent, water reducing agent, quick setting agent and polystyrene particles into 1500 parts of water and stir rapidly for 5 minutes using a handheld electric stirrer;
[0188] Step 7: Add the mixture in step 6 to the mixer to mix with the mixture in step 5, start the mixer, and mix thoroughly at 300 rpm for 10 minutes;
[0189] Step 8: Test the mortar viscosity and complete the mortar preparation.
[0190] After the mortar is prepared, it should be poured and used in time to avoid the mortar being left for a long time to solidify and stick to the mixer or container.
[0191] The performance of the mortars obtained in Examples 1-5 was tested, and the specific results are shown in Table 1.
[0192] Table 1 Mortar performance test results
[0193]
[0194]
[0195] The results in Table 1 show that the mortar obtained by the present invention has good performance and meets the use requirements. The wallboard produced by using the mortar obtained by the present invention can be used as a building wallboard for industrial and civil buildings.
[0196] The above content cannot be used to determine that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, they can make several simple deductions or substitutions without departing from the concept of the present invention, which should be regarded as belonging to the scope of patent protection of the present invention determined by the submitted claims.
Claims
1. An anti-cracking mortar for assembled lightweight partition boards, characterized in that: The invention comprises the following raw materials in parts by weight: 1600-2800 parts of silicate cement, 1-50 parts of redispersible latex powder, 1-50 parts of hydroxypropyl methylcellulose ether, 800-1500 parts of gypsum powder, 1200-2400 parts of fly ash, 8-40 parts of anti-cracking fiber, 1200-3000 parts of water, 2000-3200 parts of polystyrene particles, 600-1800 parts of light mineral waste slag, 2-3 parts of foaming agent, 2-3 parts of early strength agent, 2-3 parts of foam stabilizer, 2-3 parts of waterproofing agent, 2-3 parts of water reducing agent, 2-3 parts of accelerating setting agent and 2-3 parts of reinforcing agent.
2. The anti-cracking mortar for assembled lightweight partition boards according to claim 1, characterized in that: The anti-cracking fiber is polypropylene anti-cracking fiber.
3. The anti-cracking mortar for assembled lightweight partition boards according to claim 1, characterized in that: The foaming agent is a polyurethane foam foaming agent.
4. The anti-cracking mortar for assembled lightweight partition boards according to claim 1, characterized in that: The early strength agent is a calcium chloride antifreeze agent.
5. The anti-cracking mortar for assembled lightweight partition boards according to claim 1, characterized in that: The foam stabilizer is a foam increasing and stabilizing agent.
6. The anti-cracking mortar for assembled lightweight partition boards according to claim 1, characterized in that: The waterproofing agent is a mortar waterproofing agent.
7. The anti-cracking mortar for assembled lightweight partition boards according to claim 1, characterized in that: The water reducing agent is a naphthalene-based high-efficiency water reducing agent.
8. The anti-cracking mortar for assembled lightweight partition boards according to claim 1, characterized in that: The quick-setting agent is a liquid quick-setting agent.
9. The anti-cracking mortar for assembled lightweight partition boards according to claim 1, characterized in that: The reinforcing agent is KFA cement admixture.
10. A method for preparing the anti-cracking mortar for assembled lightweight partition boards according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1: Clean the mixer and check to make sure it is operating normally; Step 2: weigh the weight of each component according to the above components; Step 3: crush the weighed light mineral waste slag, and sieve it through a sieve of ≤3 mm to obtain light mineral waste slag powder; Step 4: first add weighed silicate cement, redispersible latex powder, hydroxypropyl methylcellulose ether, fly ash, gypsum powder, anti-cracking fiber and the light mineral waste slag powder obtained in step 3 into a mixer, stir in the mixer to fully mix the materials, and prepare a mixture a; Step 5, adding a foaming agent, an early strength agent, a foam stabilizer, a reinforcing agent and water to the mixture a obtained in step 4, and then stirring in a mixer to obtain a mixture b; Step 6: adding a waterproofing agent, a water reducing agent, an accelerating setting agent and polystyrene particles into water and stirring with a stirrer to obtain a mixture c; Step 7, adding the mixture c obtained in step 6 to the mixture b obtained in step 5, starting the mixer to stir and mix, to obtain a mixture d; Step 8: Test the viscosity of the mixture d and complete the mortar preparation.
Citation Information
Cited By
Compositions for construction and products of manufacture therefrom
WO2026053214A1